Studies on Vegetative Propagation of Balanites roxburghii Pl - Amalraj, V. A.; Shankaranarayan, K. A. (Indian Forester, 1992)
Vegetative propagation methods were tried in Balanites roxburghii every month during 1983-85. Even with external hormonal treatments of Indole Butryic Acid. Napthalene Acetic Acid and Seradix powder. Stem cuttings failed to root. But success has been achieved by adoption of ringing technique done during monsonn perind, with Seradix powder application on the, twigs covered with wet moss.